Systematic literature review of non-topical treatments for early, untreated (systemic therapy naïve) psoriatic disease: a GRAPPA initiative - De Marco, G; Berekméri, A; Coates, LC; Dubash, S; Emmel, J; Gladman, DD; Lubrano, E; McGonagle, DG; Mahmood, F; Marchesoni, A; Mason, L; Ogdie, A; et al. (Oxford University Press, 2020)
Background: Psoriatic disease (PsD) is a complex systemic disorder with cutaneous and musculoskeletal (MSK) manifestations. Current evidence on pharmacological interventions –effective Across-The-Spectrum-Of-Clinical-Manifestations (ATSOCM) of early, systemic treatment-naïve PsD- is limited. This review aims to appraise such evidence.